Effects of five preoperative cardiovascular drugs on mortality after coronary artery bypass surgery: A retrospective analysis of an observational study of 16 192 patients. Issue 1 (January 2016) - Venkatesan, Sudhir; Okoli, George N.; Mozid, Abdul M.; Pickworth, Thomas W.H.; Grocott, Michael P.W.; Sanders, Robert D.; Myles, Puja
Abstract : BACKGROUND: Statins reduce risk from coronary artery bypass graft (CABG) surgery, but the influence of angiotensin-converting enzyme inhibitors, alpha-2 adrenergic agonists, calcium channel blockers and beta-blockers is less clear. OBJECTIVES: We investigated the association of each of these drugs with perioperative risk, accounting for different confounders, and evaluated the class, dose-response and long-term protective effect of statins. DESIGN: A retrospective analysis of observational data. SETTING: United Kingdom. PATIENTS: Sixteen thousand one hundred and ninety-two patients who underwent CABG surgery during the period 01 January 2004 to 31 December 2013 and contributed data to Primary Care Clinical Practice Research Datalink. EXPOSURE VARIABLES: Cardiovascular drugs. OUTCOME MEASURE: Perioperative mortality within 30 days of surgery. STATISTICAL ANALYSIS: Five multivariable logistic regression models and a further Cox regression model were used to account for preexisting cardiovascular and other comorbidities along with lifestyle factors such as BMI, smoking and alcohol use. RESULTS: Exposure to statins was most prevalent (85.1% of patients), followed by beta-blockers (72.8%), angiotensin-converting enzyme inhibitors (60.5%), calcium channel blockers (42.8%) and alpha-2 adrenergic agonists (1.2%). The mortality rate was 0.8% in patients not prescribed statins and 0.4% in those on statins. Statins were associated with a statistically significant reduced perioperative mortality in all five logistic regression models with adjusted odds ratios (OR) (95% confidence interval, 95% CI) ranging from 0.26 (0.13 to 0.54) to 0.35 (0.18 to 0.67). Cox regression for perioperative mortality [adjusted hazard ratio (95% CI) 0.40 (0.20 to 0.80)] and 6-month mortality [adjusted hazard ratio (95% CI) 0.63 (0.42 to 0.92)] produced similar results. Of the statin doses tested, only simvastatin 40 mg exerted protective effects. The other cardiovascular drugs lacked consistent effects across models. CONCLUSION: Statins appear consistently protective against perioperative mortality from CABG surgery in multiple models, an effect not shared by the other cardiovascular drugs. Further data are needed on whether statins exert class and dose-response effects.